Constructing Resistance: A Corpus-Assisted Critical Discourse Analysis of Vernacular Agency in Cameroon’s Anglophone Digital Activism - Maiwong, Eric Dzeayele (International Journal of Language and Literary Studies, 2026)
This study provides a rigorous sociolinguistic examination of the constitutive role of language in the ongoing socio-political conflict in Cameroon’s Anglophone regions, positing digital activism as a primary site of discursive struggle. While scholarship has addressed historical-political dimensions, a significant gap persists in the empirical analysis of the micro-linguistic strategies through which vernacular practices enact ideological resistance and counter-hegemonic mobilisation (Blommaert, 2005; Kroskrity, 2000). Employing an integrated mixed-methods framework that synergizes Corpus Linguistics with Critical Discourse Analysis (Baker, Gabrielatos, KhosraviNik, Krzy?anowski, McEnery, & Wodak, 2008), this research analyses a specialised digital corpus of approximately 1,200 text-based items from social media, activist communiqués, and transcribed audio (2020–2025)—the Anglophone Digital Activism Corpus (ADAC). Quantitative keyword and collocation analyses identify statistically significant patterns, while subsequent qualitative analysis, guided by Systemic Functional Linguistics’ transitivity model (Halliday & Matthiessen, 2014) and social actor representation (van Leeuwen, 2008), performs close readings. The findings reveal a deliberate linguistic architecture characterised by three core mechanisms: the consistent grammatical positioning of collective Anglophone actors as active agents in material processes; the strategic deployment of code-mixing and lexical innovation, using Cameroonian Pidgin English and Camfranglais to create an exclusive, authentic discursive space (Gumperz, 1982); and the use of conceptual metaphors (Lakoff & Johnson, 1980) such as EDUCATION IS SOVEREIGNTY to reframe political grievances into mobilising narratives. This paper argues that digital activism in this context is fundamentally a sociolinguistic project, contributing an empirical model for analysing the interface of grammar, digital communication, and political conflict, affirming that the struggle for power is intrinsically a struggle over representation and linguistic resource mobilisation (Bourdieu, 1991).